Synergy of Responsive Legal Principles and SPBE Governance in the Digital Era - Ulum, Bahrul; Hoesein, Zainal Arifin (Fox Justi : Jurnal Ilmu Hukum, 2025)
Indonesia's Electronic-Based Government System (SPBE) faces a critical clash: rapid technical progress is stifled by a rigid legal paradigm, creating an operational dualism between bureaucratic formalism and digital agility. This manifests as a “law avalanche,” inter-ministerial fragmentation, and “legal friction,” eroding innovation, trust, and certainty. This study aims to analyze the dynamics and formulate an operational model for synergizing responsive legal principles with SPBE governance in Indonesia's digital context. Employing a qualitative exploratory case study, data were gathered via semi-structured interviews with 10 key stakeholders (policymakers, implementers, academics, CSOs, consultants) and document analysis, analyzed thematically using the Braun & Clarke model. The research identifies operational dualism and regulatory proliferation as the root cause. The solution is a Responsive Trilogy Model: (1) a Cross-Ministry Co-Regulation Protocol for joint standards; (2) ‘Compliance by Design’ integrated into agile development sprints; and (3) a Rapid Regulatory Dispute Forum with binding 30-day decisions. Its success hinges on cultivating “regulatory champions” hybrid law-technology experts. The study concludes that true synergy requires a paradigm shift from static “law as a fence” to adaptive “law as a platform,” establishing responsive law as the core architectural principle for legitimate and effective digital-era governance.